THE LAWFUL CONSEQUENCES OF BIRTH CERTIFICATE ON CHILDREN ABROGATION - Sandjojo, Natasya Immanuela (Tadulako University, 2017)
Research due to the law on the abrogation of birth certificates against children aims to know the effect of law affecting the child, as well as review of the determination and judgment in court that play a role in the birth certificate abrogation. This research describes the importance of birth certificate because of the low public awareness to perform birth registration. The study uses normative juridical research, which faces legal issues with the process of discovering legal rules, principles, and legal doctrines, with deductive methods, starting from the general thing and then generating specific and legitimate answers. Based on the results of the study, that the abrogation of birth certificate brings great lawful consequences for the child, especially the status and position of the child, as well as the right of alimentation,Â which in this study included some examples of determination and court decision about the birth certificate abrogation.